AR-JarKom: Enhanced Mobility of Computer Network Learning - Akrimullah Mubai; Elfi Tasrif; Asrul Huda; Naseh Ulwan; Yulia Mandasari; Kyaw Zay Ya (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2025)
The limited use of practicum tools in the laboratory is a problem in learning Computer Networks. In addition to the limited number, prices, and regulations also limit their use. Whereas Computer Network learning is very dependent on practicum tools. For this reason, this research aims to create an application that is able to present practicum tools whenever and wherever students want to learn Computer Networks. The application is called AR-JarKom which stands for Computer Network-based Augmented Reality in Indonesian. The AR-JarKom application is made using a waterfall model with the stages of needs analysis, design stages, development stages, testing stages, and maintenance stages. The result of this research is an AR-JarKom application that is able to display 3D objects and videos of practicum tools from Computer Network learning. Computer Network learning tools or videos can be displayed only by scanning images of tools in the printed or digital version of the labsheet. The AR-JarKom application can be run on Smartphone devices with the Android operating system. This makes student mobility to learn Computer Networks better without having to rely on practicum tools in the laboratory. Therefore, the results of this study are expected to be one of the qualified options in increasing the effectiveness of Computer Network learning. In the future, the AR-JarKom application will continue to be developed to improve its capabilities and existence.